2012
DOI: 10.1155/2012/405812
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Comparison of the AMBU AuraOnce Laryngeal Mask and the LMA Unique Laryngeal Mask Airway in Spontaneously Breathing Adults

Abstract: We conducted a randomised single-blind controlled trial comparing the LMA-Unique (LMAU) and the AMBU AuraOnce (AMBU) disposable laryngeal mask in spontaneously breathing adult patients undergoing general anaesthesia. Eighty-two adult patients (ASA status I–IV) were randomly allocated to receive the LMAU or AMBU and were blinded to device selection. Patients received a standardized anesthetic and all airway devices were inserted by trained anaesthetists. Size selection was guided by manufacturer recommendations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…. Five clinical studies compared the AuraOnce with the LMA Classic; three studies compared the AuraOnce, LMA Unique and Soft Seal; and a further study compared the AuraOnce with the LMA Unique. Our risk of bias assessments are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…. Five clinical studies compared the AuraOnce with the LMA Classic; three studies compared the AuraOnce, LMA Unique and Soft Seal; and a further study compared the AuraOnce with the LMA Unique. Our risk of bias assessments are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Four clinical trials compared the AuraOnce and the LMA Unique in adults. A pooled analysis from these four trials showed that the AuraOnce provided a higher oropharyngeal leak pressure (304 participants, mean (95% CI) difference 3.1 (1.6–4.7) cmH 2 O, p < 0.0001].…”
Section: Resultsmentioning
confidence: 99%
“…The typical incidence of blood on the i-gel at removal is between 4% and 13% [ 58 60 ] but has been reported to be as high as 20%, albeit in novice users [ 61 ]. The AuraOnce laryngeal mask was associated with a very low (2%) incidence of blood staining after its removal [ 62 ] but reached 10% in another study [ 63 ]. The presence of blood on the Cobra airway may be as high as 50% [ 64 ].…”
Section: Complicationsmentioning
confidence: 99%
“…The insertion time and success rate of the first and final LMA insertion attempts were reported to be between 11.2AE2.7 and 27.0AE10.0 seconds in previous studies. [25][26][27] Studies showed that the success rate of the first insertion attempt ranged from 83% to 92.5% [25][26][27] in adults and 93% to 100% 7,25,27,28 in children, while the success rate of final insertion was an average of 98%. 26,29 In the present study, the LMA insertion time was 35.6 AE 7.1 seconds, which is slightly longer than that of the ETI (31.2 AE 6.0 seconds).…”
Section: Discussionmentioning
confidence: 99%